2020
DOI: 10.3390/d12090318
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Managed Honey Bee Colony Winter Losses (Apis mellifera) in China (2013–2017)

Abstract: Surveys of managed honey bee colony losses worldwide have become fundamental for engineering a sustainable and systematic approach to protect honey bees. Though China is a member of the world’s apiculture superpowers, the investigation of honey bee colony losses from Chinese government was not formally launched until recently. In this study, we investigated the colony winter losses of the western honey bee (Apis mellifera) of four consecutive years in 2013–2017 from 19 provinces in China, with a total of 2387 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
4
18
1
Order By: Relevance
“…This would be consistent with the claim that China is the largest pollen producer in the world (Yang et al, 2013). China has about 9 million managed honey bee colonies (FAOSTAT, 2018) (Tang et al, 2020). 5000 metric tons is a high but plausible value of 0.6 kg of pollen per hive.…”
Section: Quantity Of Pollen Produced By Locationsupporting
confidence: 85%
“…This would be consistent with the claim that China is the largest pollen producer in the world (Yang et al, 2013). China has about 9 million managed honey bee colonies (FAOSTAT, 2018) (Tang et al, 2020). 5000 metric tons is a high but plausible value of 0.6 kg of pollen per hive.…”
Section: Quantity Of Pollen Produced By Locationsupporting
confidence: 85%
“…Many studies reported showed the colony losses of honey bees with ranges 8-50% [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In contrast, [33] reported that 42% of monitored countries (27 countries) showed an increasing trend in genetic diversity of the honey bee population.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that the business of beekeepers tends to develop by increasing the numbers of bee colonies, particularly of stingless bees. However, their operation size is still smaller than the operation size of most beekeepers in other countries [19,28,29]. Most Indonesian beekeepers were stationary beekeepers with a low risk of loss of colonies than migratory beekeepers [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of pollinator losses in the previous decade, including wild bee declines (23%), and modern bee colony losses (40% yearly winter fatality) (Metz et al, 2020). Many researchers conducted worldwide studies on honey bee colony mortality from a number of perspectives, including the global transmission of diseases and pests through the commerce in bees and bee products (Currie et al, 2010;Brodschneider et al, 2018;Castilhos et al, 2019;Tang et al, 2020). The decline in the honey bee population does not just affect pollination but also the economic entity of their keepers.…”
Section: Introductionmentioning
confidence: 99%